2023
DOI: 10.1177/09564624231162426
|View full text |Cite
|
Sign up to set email alerts
|

Suspected case of monkeypox reinfection versus reactivation in a immunocompetent patient, Barcelona, 2022

Abstract: Vaccines against smallpox are known to have cross-protective activity against monkeypox, and smallpox and monkeypox infections are believed to generate permanent immunity. Nevertheless, there are scarce data about the possibility of reinfection or reactivation. Recently, a case of apparent monkeypox reinfection has been reported. We present a suspected case of second episode of monkeypox in a healthy and previously vaccinated man, with a confirmed primary monkeypox infection occurring three months before the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Given that the cases of reinfection and breakthrough infection of MPXV among vaccinated individuals, 12–17 potential safety concerns, 18 and risk for lack of effectiveness and relatively low levels of neutralizing antibodies against MPXV induced by JYNNEOS and ACAM2000, 25 it becomes obvious that smallpox vaccines and natural immunity sometimes might fail in providing enough protection against MPXV. Therefore, MPXV vaccines should be based more on specific and designated targets instead on attenuated viruses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that the cases of reinfection and breakthrough infection of MPXV among vaccinated individuals, 12–17 potential safety concerns, 18 and risk for lack of effectiveness and relatively low levels of neutralizing antibodies against MPXV induced by JYNNEOS and ACAM2000, 25 it becomes obvious that smallpox vaccines and natural immunity sometimes might fail in providing enough protection against MPXV. Therefore, MPXV vaccines should be based more on specific and designated targets instead on attenuated viruses.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the mRNA vaccine candidate MPXfus and MPXmix were capable of inducing neutralizing antibodies against poxvirus. Given that the cases of reinfection and breakthrough infection of MPXV among vaccinated individuals, [12][13][14][15][16][17] potential safety concerns, 18 and risk for lack of effectiveness and relatively low levels of neutralizing antibodies against MPXV induced by JYNNEOS and ACAM2000, 25 response to epidemics of infectious diseases. 19 Recently, four manuscripts posted on biorxiv as preprint documents and three research articles demonstrated seven mRNA vaccines against MPXV are being developed.…”
Section: Immune Sera Of Mpxfus-or Mpxmiximmunized Mice Showed Effecti...mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 10 cases of MPXV reinfection were reported in various countries including Spain, the United Kingdom, Switzerland, Nigeria, Italy, Brazil, and others. 16,[28][29][30][31][32][33] Table 2 presents basic information of these cases.…”
Section: Risk Factors and Clinical Symptoms Of Mpox Breakthrough Infe...mentioning
confidence: 99%